2011
DOI: 10.1186/1472-6831-11-31
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with self-reported number of teeth in a large national cohort of Thai adults

Abstract: BackgroundOral health in later life results from individual's lifelong accumulation of experiences at the personal, community and societal levels. There is little information relating the oral health outcomes to risk factors in Asian middle-income settings such as Thailand today.MethodsData derived from a cohort of 87,134 adults enrolled in Sukhothai Thammathirat Open University who completed self-administered questionnaires in 2005. Cohort members are aged between 15 and 87 years and resided throughout Thaila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 27 publications
1
18
1
Order By: Relevance
“…These findings concur with other studies which assessed the association between demographic, socio‐economic, psychosocial and behavioural factors on tooth loss . A study of self‐reported teeth from a large sample of Thai adults found that low income and having low education were related to having <20 remaining teeth …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These findings concur with other studies which assessed the association between demographic, socio‐economic, psychosocial and behavioural factors on tooth loss . A study of self‐reported teeth from a large sample of Thai adults found that low income and having low education were related to having <20 remaining teeth …”
Section: Discussionsupporting
confidence: 88%
“…To reduce inequalities in the provision of health services, the Thai Ministry of Public Health launched the Thai universal coverage scheme (UCS) in 2001 . There is strong empirical evidence that this scheme has increased equity in health services .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have shown associations between childhood socioeconomic status and oral health in adulthood. These previous studies, however, mostly used social class based on the fathers’ occupation or household economic status.…”
Section: Discussionmentioning
confidence: 74%
“…Socioeconomic inequalities in oral health have been demonstrated in many epidemiologic studies; lower socioeconomic groups are more likely to have poor oral health than higher ones. Moreover, there is increasing evidence that childhood socioeconomic status is associated with oral health in adulthood, although some have denied this association. A previous study showed significant associations between childhood economic status and adult oral health in Japan, where most dental care as well as medical care has been universally covered by the public health insurance system and tax transfers.…”
mentioning
confidence: 99%